USING E-PORTFOLIOS TO ENHANCE REFLECTIVE LEARNING AND GRADUATE READINESS AT MANGOSUTHU UNIVERSITY OF TECHNOLOGY: A MIXED-METHODS. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background In the evolving landscape of higher education, the integration of digital tools such as e-portfolios has gained momentum for enhancing reflective learning and preparing students for the workplace. At Mangosuthu University of Technology (MUT), there is a growing interest in how e-portfolios can support student engagement, personal development, and graduate readiness. This study investigates the effectiveness of e-portfolios in fostering reflective practice and improving employability outcomes among final-year students. Methods A mixed-methods case study design was employed, targeting final-year students, academic staff, and selected employers across three academic departments at MUT. Quantitative data were collected via structured surveys from 92 students (57% female, 43% male; aged 21–26), assessing perceptions of skill development, self-awareness, and career readiness. Qualitative data were gathered through focus group discussions with students (n = 18), and semi-structured interviews with lecturers (n = 10) and employers (n = 6). Descriptive statistics and thematic analysis were used for interpretation. Results Quantitative findings showed that 76% of students agreed that e-portfolios improved their ability to reflect critically on learning experiences. Furthermore, 68% reported increased confidence in articulating competencies during job applications, while 81% felt more aware of their personal and professional growth. Qualitative insights revealed that lecturers viewed e-portfolios as a valuable tool for assessing graduate attributes such as communication and self-regulation. Employers reported that well-curated e-portfolios offered better insights into candidates’ practical skills and motivation than traditional CVs. Conclusion The study confirms that e-portfolios enhance reflective learning and support graduate readiness at MUT. Students, lecturers, and employers acknowledged their value in bridging academic and workplace expectations. Recommendation MUT should institutionalize e-portfolio use across all programs, supported by clear guidelines, digital literacy training, and ongoing feedback. Longitudinal studies are recommended to assess long-term employability outcomes.